Investigating aqueous phase separation of pullulan from Aureobasidium pullulans and its characterization. (1st November 2019) - Singh, Ram Sarup; Kaur, Navpreet; Singh, Dhandeep; Kennedy, John F.
Highlights: Aqueous phase separation of pullulan from culture broth using PEG was successful. Aqueous phase separation of pullulan by PEG is temperature independent. Aqueous phase separation of pullulan is simple & cost-effective downstream process. Spectral attributes of APS pullulan and its characteristics justify its purity. Abstract: In the present investigation, polyethylene glycol (PEG 6000) was used for downstream processing of pullulan from Aureobasidium pullulans by aqueous phase separation (APS) technique. The cell-free broth was processed with PEG solution (10–35%, w/w) and pullulan formed a clear separate phase with all concentrations of PEG i.e. pullulan in lower phase and PEG solution along with impurities in upper phase. Maximum pullulan recovery from cell-free broth was obtained by PEG 25% (w/w). The sample handling in APS technique is quite easier due to lesser volume of PEG used in comparison to organic solvent precipitation i.e. minimum required ratio of cell-free broth to PEG for maximum pullulan yield was 0.5:1 (PEG:cell-free broth). Additionally, APS technique was found to be temperature independent. Further, structural attributes of pullulan recovered by APS was confirmed by FTIR, NMR and TLC. This is the first report on downstream processing of pullulan using PEG based aqueous solution.